Gender differences in willingness to pay for capital-intensive agricultural technologies: The case of fish solar tent dryers in Malawi - Levison S. Chiwaula; Gowokani Chijere Chirwa; Lucy S. Binauli; James Banda; Joseph Nagoli (Agricultural and Food Economics, 2018)
Gender differences in fish processors' willingness to pay for a group-owned fish solar tent dryer (FSTD) are being assessed by using the double hurdle model. Willingness to pay (WTP) responses from 382 randomly selected fish processors were elicited through a bidding game in a contingent valuation method. The findings show that the average probability that fish processors will be willing to pay was 74% (76% for females and 72% for males). Furthermore, the average level of WTP was US29.45 (US26.46 for females and US33.51 for males). Females have a lower level of WTP than men because of their low endowment with assets that can assist them such as education, access to markets and productive assets. In view of these findings, the paper concludes that female fish processors have a higher probability of being willing to pay than male fish processors, but the levels of WTP are lower for female processors. The study suggests that when organising the community into cooperatives is possible, WTP for capital-intensive technologies can be assessed as contributions of individuals to the total cost of the technologies although the common property characteristic is suspected to lower the level of willingness to pay.
Keywords: 330; Fish postharvest losses; Fish solar tent dryer; Willingness to pay; Contingent valuation; Double hurdle model; Malawi